Randomized comparative study of combination of low dose oral isotretinoin with pulsed azithromycin and low dose oral isotretinoin alone in the management of moderate to severe acne - Jindal, Rashmi; Roy, Samarjit; Jain, Akanksha (International Journal of Research in Dermatology, 2018)
Background: Oral isotretinoin and azithromycin are two important drugs used in management of acne. Their mode of action is different and thus theoretically the combination of these two should have a synergistic effect. Methods: In this randomized comparative trial 100 patients were randomized into two groups. One received oral isotretinoin (0.3 mg/kg/day) alone and the other group received pulsed azithromycin (500 mg/day for three days in a week for 8 weeks) in addition to oral isotretinoin. Improvement in acne was noted as percentage improvement in mean acne score. Results: No statistically significant difference was noted in the improvement in mean acne score of both the groups. Conclusions: Addition of pulsed azithromycin to low dose oral isotretinoin does not offer a better treatment outcome in patients of moderate to severe acne.